Komposisi fisik karkas ayam broiler yang diberi ransum mengandung sorgum (Sorghum bicolor L.) - Desrin Natalie Ngongo; Ni Made Yudiastari; Yan Tonga (GEMA AGRO, 2018)
This study used a Completely Randomized Design (CRD) with 5 treatments. In each replication using 3 broiler aged 2 weeks with homogeneous body weight. The five treatments are R0= Control rations without the addition of sorgum, R1= Rations containing 7% sorgum, R2= Rations containing 14% sorgum, R3= Rations containing 21% sorghum, and R4= Rations containing 21% sorgum. Parameters observed physical composition of chest and thigh carcasses. The data obtained were analyzed by variance, if the data obtained were significantly different (P 0.05) on physical composition of the carcass of the chest and thighs of broiler.